Penerapan Progressive Muscle Relaxation Terhadap Penurunan Kadar Glukosa Darah Pada Penderita Diabetes Melitus Tipe 2 di RSUD Dr Moewardi Surakarta - Agus Waluyo Sejati; Fida’ Husain; Suciana Ratrinaningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Type 2 diabetes mellitus is a type of metabolic disorder characterized by hyperglycemia which leads to serious complications. One physical activity that can be applied is progressive muscle relaxation, which focuses on sequentially tightening and relaxing muscle groups resulting in controlled blood glucose levels so that holistic treatment is needed. Objective: To determine the results of the application of Progressive Muscle Relaxation (PMR) to reduce blood glucose levels in people with type 2 diabetes mellitus at RSUD Dr. Moewardi Surakarta. Method: This research is a type of qualitative descriptive research with a case study approach (Case Study). The design for this application was a control group design which was applied to 1 respondent with Diabetes Mellitus Type 2. Results: Based on the results of this application, it was found that blood glucose levels decreased after Progressive Muscle Relaxation was carried out, which was indicated by the number of high glucose levels decreasing. Comparison before and after applying Progressive Muscle Relaxation, before being given the application of PMR high blood sugar levels were 415 mg/dl and after being given the application of PMR 2 times a day (morning and evening) for 3 consecutive days normal blood sugar levels were 173 mg/dl etc. Conclusion: Blood sugar levels before the application were given were high and after the application was given the patient's blood sugar levels were normal.